KAJIAN MIMESIS REFLEKSI DAN REFRAKSI REALITAS IMAJINATIF DAN REALITAS OBJEKTIF NOVEL WARISAN CHAIRUL HARUN - darussalam, zulfardi (Jurnal KATA, 2017)
This research used to use nimesis approach with descriptive qualitative method wich described the social phenomena in a novel. These phenomena are (1) the illegal sex intercourse, (2) the divorcement (3) the system of patrimony sharing, and (4) the family relationship. The data are consist of the imaginative reality data which came from Warisan, a novel by Charul Harun, (2) the objective reality which are obtained from 30 teachers of secondaries schools (SLTA dan SLTP)  in Bukttinggi. Both of these data were analysed and compared. The finding show that the imaginative reality is the reflection and refraction of the objective reality. As the conclusion, Warisan was a reflection of social problems which found in the society.